Fostering Digital Education among Teachers and Learners in Sri Lankan Schools - Shironica Priyanthi Karunanayaka (Commonwealth of Learning, 2020)
The Commonwealth Digital Education Leadership Training in Action (C-DELTA) programme provides a framework for fostering digital education for lifelong learning by developing digital education leaders. The Faculty of Education at the Open University of Sri Lanka implemented an action research project to promote the adoption of C-DELTA among teachers and students of secondary schools in Sri Lanka, and evaluate its impact on the teaching-learning process. A group of 41 teachers participated in the intervention and implemented C-DELTA in their schools. A variety of data were collected throughout the process via questionnaires, concept maps, focus group interviews, implementation reports, and log records in the C-DELTA platform. Findings revealed that despite challenges such as inadequate ICT facilities, time constraints and limitation in English language competencies, the adoption of C-DELTA has supported improving digital literacy, enacting changes in thinking and digital behaviour among teachers and students, and enhancing teachers’ digital education leadership skills.